EAACI Food Allergy and Anaphylaxis Guidelines: diagnosis and management of food allergy. Issue 8 (9th June 2014) - Muraro, A.; Werfel, T.; Hoffmann‐Sommergruber, K.; Roberts, G.; Beyer, K.; Bindslev‐Jensen, C.; Cardona, V.; Dubois, A.; duToit, G.; Eigenmann, P.; Fernandez Rivas, M.; Halken, S.; et al.
Abstract Food allergy can result in considerable morbidity, impact negatively on quality of life, and prove costly in terms of medical care. These guidelines have been prepared by the European Academy of Allergy and Clinical Immunology's (EAACI) Guidelines for Food Allergy and Anaphylaxis Group, building on previous EAACI position papers on adverse reaction to foods and three recent systematic reviews on the epidemiology, diagnosis, and management of food allergy, and provide evidence‐based recommendations for the diagnosis and management of food allergy. While the primary audience is allergists, this document is relevant for all other healthcare professionals, including primary care physicians, and pediatric and adult specialists, dieticians, pharmacists and paramedics. Our current understanding of the manifestations of food allergy, the role of diagnostic tests, and the effective management of patients of all ages with food allergy is presented. The acute management of non‐life‐threatening reactions is covered in these guidelines, but for guidance on the emergency management of anaphylaxis, readers are referred to the related EAACI Anaphylaxis Guidelines.